The genome-wide transcription response to telomerase deficiency in the thermotolerant yeast Hansenula polymorpha DL-1 - Beletsky, Alexey V. (BMC Genomics, 2017)
BACKGROUND: In the course of replication of eukaryotic chromosomes, the telomere length is maintained due to activity of telomerase, the ribonucleoprotein reverse transcriptase. Abolishing telomerase function causes progressive shortening of telomeres and, ultimately, cell cycle arrest and replicative senescence. To better understand the cellular response to telomerase deficiency, we performed a transcriptomic study for the thermotolerant methylotrophic yeast Hansenula polymorpha DL-1 lacking telomerase activity. RESULTS: Mutant strain of H. polymorpha carrying a disrupted telomerase RNA gene was produced, grown to senescence and analyzed by RNA-seq along with wild type strain. Telomere shortening induced a transcriptional response involving genes relevant to telomere structure and maintenance, DNA damage response, information processing, and some metabolic pathways. Genes involved in DNA replication and repair, response to environmental stresses and intracellular traffic were up-regulated in senescent H. polymorpha cells, while strong down-regulation was observed for genes involved in transcription and translation, as well as core histones. CONCLUSIONS: Comparison of the telomerase deletion transcription responses by Saccharomyces cerevisiae and H. polymorpha demonstrates that senescence makes different impact on the main metabolic pathways of these yeast species but induces similar changes in processes related to nucleic acids metabolism and protein synthesis. Up-regulation of a subunit of the TORC1 complex is clearly relevant for both types of yeast. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-017-3889-x) contains supplementary material, which is available to authorized users.